Techno‐Social Contracts for Security Orchestration in the Future of Systems Engineering. Issue 1 (30th September 2020) - Dove, Rick; Willett, Keith D.
Abstract: Security orchestration is the command and control behind security operations. Command includes governance and adjudication logic and rules. Control includes the messaging infrastructure and message set for bidirectional communication between the orchestration engine and the constituent parts of its enclave. Open Command and Control (OpenC2) 1 is one effort advancing the messaging infrastructure and message set. Automating the command portion of orchestration remains largely unexplored and will emerge as a symbiosis between people and technology. Technology will have some autonomy including the ability to establish and sustain relationships (argued in a social sense) with other technology. To help facilitate trust relationships and interactions that secure the respective systems and their environment, techno‐social contracts are explored as an approach to explicitly encode technology‐to‐technology rules of intra‐protection and inter‐protection as part of security orchestration.